If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3m + 1) + -2(2m + 3) = 3(m + 4) + 2 + 7 Reorder the terms: 4(1 + 3m) + -2(2m + 3) = 3(m + 4) + 2 + 7 (1 * 4 + 3m * 4) + -2(2m + 3) = 3(m + 4) + 2 + 7 (4 + 12m) + -2(2m + 3) = 3(m + 4) + 2 + 7 Reorder the terms: 4 + 12m + -2(3 + 2m) = 3(m + 4) + 2 + 7 4 + 12m + (3 * -2 + 2m * -2) = 3(m + 4) + 2 + 7 4 + 12m + (-6 + -4m) = 3(m + 4) + 2 + 7 Reorder the terms: 4 + -6 + 12m + -4m = 3(m + 4) + 2 + 7 Combine like terms: 4 + -6 = -2 -2 + 12m + -4m = 3(m + 4) + 2 + 7 Combine like terms: 12m + -4m = 8m -2 + 8m = 3(m + 4) + 2 + 7 Reorder the terms: -2 + 8m = 3(4 + m) + 2 + 7 -2 + 8m = (4 * 3 + m * 3) + 2 + 7 -2 + 8m = (12 + 3m) + 2 + 7 Reorder the terms: -2 + 8m = 12 + 2 + 7 + 3m Combine like terms: 12 + 2 = 14 -2 + 8m = 14 + 7 + 3m Combine like terms: 14 + 7 = 21 -2 + 8m = 21 + 3m Solving -2 + 8m = 21 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -2 + 8m + -3m = 21 + 3m + -3m Combine like terms: 8m + -3m = 5m -2 + 5m = 21 + 3m + -3m Combine like terms: 3m + -3m = 0 -2 + 5m = 21 + 0 -2 + 5m = 21 Add '2' to each side of the equation. -2 + 2 + 5m = 21 + 2 Combine like terms: -2 + 2 = 0 0 + 5m = 21 + 2 5m = 21 + 2 Combine like terms: 21 + 2 = 23 5m = 23 Divide each side by '5'. m = 4.6 Simplifying m = 4.6
| (8m+3n)(2m+5n)= | | 4x+9=10x+5 | | x^4+11x^2-900=0 | | (8m+3n)(x+6)= | | 2sec(x)tan(x)=0 | | 35-k= | | -2x^2+16x-40=0 | | 4x+11=7x+5 | | 2x+9=7x+3 | | 3/4x8x | | (4a+8x)(7a-5x)= | | -1(x-y)+3(y-x)= | | (2w+2b)(3w+5b)= | | (ln(4)^2/(2ln2)-(ln(2)^2)/(2ln2) | | 30=3x-9 | | 2lnx-6=0 | | -5=0.25(4t+20r)-8r | | 1-4x/2x-1 | | 8sinx+16=20 | | t(2+-5t+3t^2)=0 | | 8+3x=x | | n^2+4n+16=0 | | 15z-(-3x-10x)= | | 2x^2+28=1 | | 3x-5y=42 | | n^3-64=0 | | X-0.6x=12 | | h^2+6h+9= | | 3x^2-60x+400=0 | | 7a+4b=32 | | 3(2x-4y)-2(2x-5y)+2y= | | ln(4x+5)=ln(2x-1)+ln(3) |